Perceived stress and depression during covid-19 among senior citizen residing at old age home of Kaski and Tanahun districts. - Khanal, Deepa (2020)
ABSTRACT: Introduction: Due to growing age, many older people are tends to be at risk of developing mental disorders as well as other health conditions. Perceived stress and depression has been recorded as a common health problem which is a major cause of mortality, morbidity and disability worldwide. These day's most of the elderly people are isolated from families, community, and from country too. Due to which these groups age 60 years and above may be more vulnerable than others to the psychosocial effects of pandemics like COVID-19. The aim of the study was to assess the perceived stress level and depression during COVID19 among senior citizen residing at old age home of Kaski and Tanahun districts. Methods and material: The study was cross-sectional study design and the study population was the senior citizens who were 60 years old or above currently living in old aged homes of Kaski and Tanahun districts. The Perceived Stress Scale (PSS) and Geriatric depression scale short form (GDS-15) score was used to identify the prevalence of perceived stress and geriatric depression respectively. Data were entered in Epi-data software and analyzed using SPSS statistics software. Results: The study found that the prevalence of perceived stress among the senior citizen of old age homes was 60.4% which includes 54% had moderate perceived stress and 6.4% had high perceived stress. Also, the prevalence of depression was 34.2% which includes 25.7% had moderate depression and 8.5% had severe depression. Gender, satisfaction with the environment inside old age homes and satisfaction with the health care facilities availability and provided during covid-19 are significantly associated with perceived stress. Finding from the study shows that there is a positive correlation between perceived stress and depression among the senior citizen residing at old age home during Covid-19. Conclusion: More than half of participants of the senior citizen were suffering from perceived stress and one third of the population of the senior citizen were suffering from depression. Perceived stress during covid-19 was significantly associated with gender, satisfaction with the environment and facilities availability inside old age homes.